ILLUMINATING SURGICAL DEVICE - KUSTERS, Roel, H; SMITS, Edsger; HARKEMA, Stephen; DOBROVOLSKIS, Paul; DUGGAL, Anil (2023)
Embodiments of claimed subject matter are directed to an illuminating surgical device comprising an array of illuminating elements and an array of louvers to direct light from the individual illuminating elements toward a surgical field.